The Microfacies Analysis and Depositional Environment of the Middle-Late Oligocene Al Abraq Formation, N Cyrenaica Promontory, Northeast Libya - Zafir, Akram; Ahmed Abuharara; Ayman Nassar (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. The present study reports the depositional processes and environment of the Middle-Late Oligocene Al Abraq Formation in northeast Libya. Methods. This study provides a detailed facies analysis to precisely interpret the paleoenvironmental context during their deposition, through out three measured sections located in N Cyrenaica Promontory. Results. Five distinct microfacies were defined based on variations in lithology, fossil content, grain composition, sedimentary texture, color, and lateral and vertical changes. Al Abraq Formation is mainly composed of yellowish white, soft to moderately hard limestone. The microfacies analysis of the studied carbonate rocks (Al Abraq Formation) enables determination of three shallow-marine carbonate facies associations: restricted a lagoon, open marine, and slope. The restricted lagoon consists mainly of foraminifera, algae, and gastropods, which indicates shallow open-marine environment above fair-weather wave base. The open marine characterized by accumulation of large quantities of glauconite which has microfossils’ record that represented by gastropods, foraminifera, and echinoderms .The slope facies association consists of high percentages of larger foraminifera and some of these particles are echinoderm fragments and algae that may have formed in the upper part of the slope where the reworking of sediments by currents or storms is high. Conclusion. Microfacies of the Al Abraq Formation exhibits biotic elements that indicate shallow open shelf settings. Cite this article. Zafir A, Abuharara A, Nassar A. Microfacies Analysis and Depositional Environment of the Middle-Late Oligocene Al Abraq Formation, N Cyrenaica Promontory, Northeast Libya. Alq J Med App Sci. 2022;5(2):517-526. https://doi.org/10.5281/zenodo.7245834